The Effect of Fly Ash Ratio Addition as Layering Material Using Free Draining Column Leach Test Method on Laboratory Scale - Harnanda, Suriandi; Kusuma, Ginting Jalu; Badhurahman, Abie; Syaputra, Rizky (EKSPLORIUM, 2023)
Acid mine drainage (AMD) is formed due to the oxidation of sulfide minerals in the presence of water and air. AMD already entering the environment can damage the aquatic ecosystem due to low pH and high dissolved metal concentrations. Efforts to prevent the formation of AMD are by regulating the stockpiling of materials containing sulfide or potential acid forming (PAF) with non-acid forming (NAF) to avoid oxidation reactions of sulfide minerals. The purpose of this study was to simulate the effect of adding fly ash ratio as a PAF rock coating material to the quality characteristics of leachate using the laboratory-scale free draining column leach test (FDCLT) method. Adding fly ash ratio as a layering material significantly affects the quality of the resulting leachate. This is due to the physical condition of the fly ash material, which cannot prevent the meeting of AMD-forming components.